Adsorption of micronutrient metal ion onto struvite to prepare slow release multielement fertilizer: Copper(II) doped-struvite - Arslanoglu, Hasan (Pergamon-Elsevier Science Ltd, 2019)
In this study, struvite (MgNH4PO4 center dot 6H(2)O) sample was prepared by precipitation. Synthetic struvite was used as an adsorbent to remove Cu(lI) from aqueous solution. Struvite was characterized by X-ray diffraction, FTIR, particle size analysis, SEM-EDX, surface area and true density. Solubility of struvite in water and acid solutions was investigated. Batch adsorption experiments were carried out by changing the initial Cu(lI) concentration, contact time, struvite dosage and temperature. Cu(II) adsorption was found to be highly pH-dependent, and maximum adsorption was observed in the basic pH range. Equilibrium data were applied to Langmuir, Freundlich and D-R adsorption isotherms. Kinetic data were also analyzed for pseudo-first, pseudo-second and intraparticle diffusion models. Langmuir adsorption isotherm and pseudo-second kinetic models fit best to the data. Maximum adsorption capacity was found to be 158.73 mg g(-1), at 20 degrees C, pH of 6 and adsorbent dosage of 1 g L-1 for a contact time of 240 min. Activation energy, mean adsorption energy (from D-R isotherm) and thermodynamic parameters were evaluated, and the nature of adsorption was found to be physical, endothermic and spontaneous. On the basis of characterization upon struvite before and after adsorption, it was found that the electrostatic attraction supported the ion sorption on struvite surface, and the transformation of Cu(II) ion into copper phosphate and copper hydroxide occurred on struvite surface. After its adsorption, solubility study was carried out. Release of P, N, Mg and Cu into extracts was studied. Phosphorus, nitrogen, magnesium and copper solubility in pure water was lower than about 1%. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Cu(II) adsorption; Dissolution; Isotherm; Kinetics; Thermodynamic parameters; Struvite